Role of P2X4/NLRP3 Pathway-Mediated Neuroinflammation in Perioperative Neurocognitive Disorders - Yuan, Hui; Lu, Bo; Ji, Yiqin; Meng, Bo; Wang, Ruichun; Sun, Daofan; Liu, Rongjun; Zhai, Xiaojie; Li, Xiaoyu; Qin, Jinling; Chen, Junping (Mediators of Inflammation, 2022)
Several studies have demonstrated that neuroinflammation is the key to perioperative neurocognitive disorders (PND); however, the specific mechanism postsurgery and anesthesia has not yet been fully clarified. The present study is aimed at exploring the effects of P2X4/NLRP3 signaling pathway in neuroinflammation and cognitive impairment after surgery. 12–14-month-old male C57BL/6 mice undergoing open tibial fracture surgery by sevoflurane anesthesia were administered P2X4R inhibitor 5-BDBD or saline was intraperitoneally for 3 consecutive days after surgery. Then, the animals were subjected to Morris water maze test or sacrificed to collect the hippocampus. The level of P2X4R and NLRP3 was estimated by Western blot, the activation of microglia was detected via immunohistochemistry, and the expression of TNF-α, IL-1β, and IL-6 was quantified by enzyme-linked immunosorbent assay. These results indicated that tibial surgery caused cognitive impairment, increased the expression of P2X4R and NLRP3, and aggravated the neuroinflammation and microglia activation. However, intraperitoneal injection of 5-BDBD attenuated these effects. In conclusion, these findings indicated that the P2X4/NLRP3 pathway might be involved in the pathophysiology of PND.